Enhanced solar-to-hydrogen efficiency for photocatalytic water splitting based on a polarized heterostructure: the role of intrinsic dipoles in heterostructures. Issue 25 (17th June 2021) - Liu, Xinyi; Cheng, Peng; Zhang, Xiuhai; Shen, Tao; Liu, Jia; Ren, Ji-Chang; Wang, Hongqiang; Li, Shuang; Liu, Wei
Abstract : In2 Se3 /SnP3 Z-scheme photocatalyst with a high solar-to-hydrogen (STH) efficiency of 19.26%. Abstract : Inspired by natural photosynthesis, direct Z-scheme heterostructures are considered as promising photocatalysts for solar-driven water splitting and attract ever-growing interest. To date, it is still a challenge to achieve a high efficiency based on direct Z-scheme photocatalysts for overall water splitting, because suitable band gaps and overpotentials for both half-reactions and spatially separated catalytic sites should be fulfilled simultaneously in a photocatalytic system. These challenges can be solved by taking advantage of the intrinsic dipole effect for polarized materials. Here, we propose a new strategy to achieve this goal by constructing van der Waals (vdW) heterostructures based on two-dimensional (2D) polarized materials. Using density functional theory calculations, we predict a promising photocatalyst In2 Se3 /SnP3 heterostructure, with the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) taking place separately on the SnP3 and In2 Se3 layers. It is found that the intrinsic dipole of the In2 Se3 monolayer effectively enhances the redox abilities for both the HER and OER. Moreover, the intrinsic dipole can promote the spatial separation of photogenerated carriers, and also contributes to a high solar-to-hydrogen (STH) efficiency of 19.26%, which is quite promising for commercial applications. This work opens up an avenue for the design of highly efficient Z-scheme photocatalysts for overall water splitting.